2018
DOI: 10.5337/2018.210
|View full text |Cite
|
Sign up to set email alerts
|

Water user associations: a review of approaches and alternative management options for Sub-Saharan Africa

Abstract: Working PapersThe publications in this series record the work and thinking of IWMI researchers, and knowledge that the Institute's scientific management feels is worthy of documenting. This series will ensure that scientific data and other information gathered or prepared as a part of the research work of the Institute are recorded and referenced. Working Papers could include project reports, case studies, conference or workshop proceedings, discussion papers or reports on progress of research, country-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
(226 reference statements)
1
17
0
Order By: Relevance
“…Irrigation facilities must be operated efficiently and effectively in order for WUAs providing water distribution services to continue to exist and to carry out their activities successfully. This is consistent with several reviews on WUAs in the literature that reported the two most prominent criticisms of WUAs to be found are the unrealistic expectations on cost recovery and the inability to promote an inclusive user participation during the implementation of irrigation projects (Aarnoudse et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Irrigation facilities must be operated efficiently and effectively in order for WUAs providing water distribution services to continue to exist and to carry out their activities successfully. This is consistent with several reviews on WUAs in the literature that reported the two most prominent criticisms of WUAs to be found are the unrealistic expectations on cost recovery and the inability to promote an inclusive user participation during the implementation of irrigation projects (Aarnoudse et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Most originate in the replication of unequal power relations that already exist among the community of users, in the structure of the WUA, diverging interests of users not being appropriately addressed by WUAs' leadership, and an unequal share of decision-making power, particularly with vulnerable water users (Harris, 2005;Meinzen-Dick and Zwarteveen, 1998). In addition, incomplete decentralization processes that lead to discrepancies between the expected benefits of implementing a "participatory model" and the realities in operating the WUAs in local contexts have also been recognized as limitations of WUAs to deliver increased and more equitable participation of water users (Aarnoudse et al, 2018;Harris, 2006;Senanayake et al, 2015;Upadhyay, 2003). This creates the risk of deepening existing social asymmetries and inequalities (Zwarteveen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is often believed that PIM contributes to better water management, reduced government operations cost, greater sustainability and better accountability [5][6][7]. The WUAs are expected to have inclusive user participation, full cost recovery, operation and maintenance (O&M), and reliable service provision [8]. The experience varies depending on factors such as the institutional and legal framework, financial resources, technical resources and support services, and local leadership.…”
Section: Background Of Participatory Irrigation Management (Pim)mentioning
confidence: 99%